In Vivo Luminescence Nanothermometry: from Materials to Applications. Issue 1 (11th October 2016) - del Rosal, Blanca; Ximendes, Erving; Rocha, Ueslen; Jaque, Daniel
Abstract : The current status of the use of luminescent nanoparticles for thermometry in animal models is reviewed in detail. The different types of luminescent nanoparticles capable of deep tissue temperature sensing are described, paying special attention to the physical mechanisms at the root of their thermal sensing capacity. Their thermal sensitivities are listed and compared. This review describes the most relevant experiments, in which luminescence nanothermometry has been successfully applied at the small animal level, including the development of controlled thermal therapies as well as subtissue diagnosis procedures. Advantages and disadvantages of different luminescent nanothermometers are discussed. Abstract : Luminescence nanothermometry is attracting a growing interest for in vivo applications as new temperature‐sensitive fluorescent probes operating in the biological windows are developed. The fundamentals behind the operation of these IR‐absorbing, IR‐emitting nanothermometers are presented. Additionally, their application in temperature control during thermal therapy and in studies of thermal dynamics in animal models are reviewed in this work.